The AMPylase FIC-1 modulates TGF-β signaling in Caenorhabditis elegans - Hernandez-Lima, Mirella A.; Champion, Margaret; Mattiola, Zachary; Truttmann, Matthias C. (Frontiers in Molecular Neuroscience, 2022)
Post-translational protein modifications are essential for the spatio-temporal regulation of protein function. In this study, we examine how the activity of the Caenorhabditis elegans AMPylase FIC-1 modulates physiological processes in vivo. We find that over-expression (OE) of the constitutive AMPylase FIC-1(E274G) impairs C. elegans development, fertility, and stress resilience. We also show that FIC-1(E274G) OE inhibits pathogen avoidance behavior by selectively suppressing production of the Transforming Growth Factor-β (TGF-β) ligands DAF-7 and DBL-1 in ASI sensory neurons. Finally, we demonstrate that FIC-1 contributes to the regulation of adult body growth, cholinergic neuron function, and larval entry into dauer stage; all processes controlled by TGF-β signaling. Together, our results suggest a role for FIC-1 in regulating TGF-β signaling in C. elegans.